SOCIAL PEDAGOGY: PROBLEMS AND SOLUTIONS - Ibodullayeva Zubayda Sherzodovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
The exploration of social pedagogy reveals a landscape where education, health, and social welfare intersect, presenting both significant challenges and transformative opportunities. In addressing systemic issues, social pedagogy emphasizes holistic approaches that integrate community engagement and educational frameworks. For instance, through social prescribing, healthcare systems are increasingly connecting individuals to community programs that address unmet social needs, highlighting the potential of arts in health, such as music interventions, to enhance well-being (Aitcheson et al., 2025). Nonetheless, implementing these practices often encounters resistance due to entrenched traditional methods and a lack of institutional support (Makhasane et al., 2025). Furthermore, the democratic management of educational environments reveals that fostering genuine student partnerships can enhance learning experiences, though communication barriers remain a challenge (Maharajan et al., 2025). These interconnected dynamics underscore the necessity for updated educational policies that reflect the values of collaboration, inclusivity, and support, as represented in , particularly in mentoring contexts where holistic approaches are crucial.